4.


x(k) := xmn x(k) = xmn
렠 next k
return
4. ,
(1)' £ (2)' £ ... £ x(N)'
L[1:N],
x(k)' = p(L(k)) k = 1, .... N.
. ­ (1)' £ (2)' £... £ x(N)' x[l:N] . :
Imn := L(imn) Imn = L(imn)
xmn
:= x(imn) xmn = x(imn)
L(imn) := L(k) L(imn)' = L(k)
x(imn) := x(k) x(imn)' = x(k)
L(k) := Imn L(k)' = Imn = L(imn)
x(k) := xmn x(k)' = xmn = x(imn)
L[1:N] ­ x[l:N] , ­ :
(i)' = P(L(i) i = 1, ..., N.
, . , k- :
Imn = L(imn)
xmn = x(imn) == p(L(imn))
L(imn)' = L(k)
x(imn)' = x(k) = p(L(k)) = p(L(imn)')
L(k)' = Imn = L(imn)
x(k)' = xmn = x(imn) = p(L(imn)) = p(L(k)')
,